Partial budget analysis for on-station and on-farm small ruminant production systems research: Method and data requirements - Ehui, Simeon K.; Rey, B. (International Livestock Centre for Africa, 1992)
Economic constraints and opportunities for improving small ruminant production systems in sub-Saharan Africa must be understood as the basis for developing interventions. However, most national agricultural research systems (NARS) face a shortage of livestock economists, and biological scientists often lack the skills needed to conduct an economic evaluation of the results of their work. This study presents the partial budget analysis (PBA) framework for the economic analysis of small ruminant interventions for use by livestock specialists. The logic of the PBA and the data needs are discussed first. This is followed by an empirical example which analyses the economics of endoparasite control in sheep production system of the Ethiopian highlands. The analysis is based on experimental data from ILCA's Debre Birhan station. The experiment consisted of four treatments: I. Grazing natural pasture; II. Drenching with anthelminthics; III. Supplemental feeding with wheat bran and noug (Guizotia abyssinica) cake; IV. Supplemental feeding and drenching. Results show that net returns per ewe of treatments II, III and IV exceeded the net return of the control by Ethiopian birr (EB) 4.86, 8.56 and 9.35, respectively (US$ 1 = EB 2.07). The increase in cost for treatment II relative to the control was EB 1.44; the added net benefit from this treatment was EB 4.86 per ewe, giving a marginal rate of return of 334%. The increase in cost of treatment III relative to treatment II was EB 19. 60, while the increase in net return was EB 3. 71 per ewe, giving a marginal rate of return on the increased expenditure of 19%. The cost of adding drenching to treatment III (treatment IV) was EB 3.58 per ewe, while the increase in net return relative to treatment III was EB 0.78 for a marginal rate of return of 22%. The marginal rate of return of treatment IV relative to treatment III was 19.4%. Given the high cost of capital, treatments III and IV cannot be recommended. Drenching alone (treatment II) yielded a very high marginal rate of return under experimental conditions and should be tested under on-farm conditions .